TWEAK/Fn14 signalling promotes cholangiocarcinoma niche formation and progression - Dwyer, Ben; Jarman, E.J.; Gogoi-Tiwari, Jully; Ferreira-Gonzalez, S.; Boulter, L.; Guest, R.V.; Kendall, T.J.; Kurian, D.; Kilpatrick, A.M.; Robson, A.J.; O'Duibhir, E.; Man, T.Y.; et al. (ELSEVIER, 2021)
Background & Aims: Cholangiocarcinoma (CCA) is a cancer of the hepatic bile ducts that is rarely resectable and is associated with poor prognosis. Tumour necrosis factor-like weak inducer of apoptosis (TWEAK) is known to signal via its receptor fibroblast growth factor-inducible 14 (Fn14) and induce cholangiocyte and myofibroblast proliferation in liver injury. We aimed to characterise its role in CCA.